PENGENALAN PENDIDIKAN DASAR BAGI ANAK MARGINAL SEBAGAI PENERAPAN SDG DI GROGOL - Nurfakhira, Callista; Lukman, Hendro (Jurnal Serina Abdimas, 2024)
Every child is born to get the rights from their parents, starting from the right to get a name or identity, the right to get protection, the right to get education, and others. One of the rights of children that is often ignored is to get a proper education. Economic, family, and environmental factors are the main that should be fixed. The government’s efforts in terms of education equity are still being carried out, such as providing free schools and providing scholarship programs. Marginalized children or street children are the main focus in this conditions. At the age of those who are supposed to study, they are forced to work. Humanitarian project activities are carried out as a form of concern for fellow individuals. Contribute directly in guiding and providing basic education, especially to early childhood. Education that has been attached will have a big impact on their life in the future. The purpose of this activities are expected to change the mindset and character of marginalized children become more better, reduce underage workers on the streets, and increase children's enthusiasm in learning because of fun activities. In addition, this activity is also an implementary of the Sustainable Development Goals in terms of providing quality education. This activity starts from August , 2023 to October , 2023. It begins with basic learning, such as reading, writing, and counting. Then, continued with learning while playing. With humanitarian project activities, the benefits that can be felt are developing creativity in providing material, understanding the character of each individual and learning to control emotions, and can increase insight and enthusiasm for learning.